2015
DOI: 10.1055/s-0034-1397344
|View full text |Cite
|
Sign up to set email alerts
|

Overview of MicroRNA Biology

Abstract: In considering an overview of microRNA biology, it is useful to consider microRNAs as a part of cellular communication. At the simplest level, microRNAs act to decrease the expression of mRNAs that contain stretches of sequence complementary to the microRNA. This function can be likened to the function of endogenous or synthetic short interfering RNA (siRNA). However, microRNA function is more complicated and nuanced than this ‘on-off’ model would suggest. Further, many microRNA targets are themselves non-codi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
644
0
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 931 publications
(656 citation statements)
references
References 74 publications
3
644
0
9
Order By: Relevance
“…MiRNAs are recognized to regulate the expression of approximately 30% of human proteins and participate in a variety of biological processes, such as cell proliferation, differentiation, migration and apoptosis [10]. miRNA-214 is involved in myogenesis, gonadogenesis and trophectoderm determination, and it plays a significant role in cell fate during genesis and development of tissues and organs [11, 12]. Mitofusin2 (Mfn2) is a guanosine triphosphatase (GTPase) dynamin-like protein of the outer mitochondrial membrane, and mutations in genes that encode Mfn2 can be associated with neurological disorders [13].…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are recognized to regulate the expression of approximately 30% of human proteins and participate in a variety of biological processes, such as cell proliferation, differentiation, migration and apoptosis [10]. miRNA-214 is involved in myogenesis, gonadogenesis and trophectoderm determination, and it plays a significant role in cell fate during genesis and development of tissues and organs [11, 12]. Mitofusin2 (Mfn2) is a guanosine triphosphatase (GTPase) dynamin-like protein of the outer mitochondrial membrane, and mutations in genes that encode Mfn2 can be associated with neurological disorders [13].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are non-coding RNAs that regulate gene expression by binding to mRNA, stopping translation or degrading the mRNAs. These functions are mainly achieved by the binding of mi-RNAs with the 3'-UTR of mRNAs [11]. MiRNAs have recently been implicated in inflammatory responses, sepsis, and, specifically, macrophage activities [9,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, it has been shown that genes have multiple modalities in transcriptional regulation (Oh‐Hashi et al, ). As one of the important regulators, microRNA is a short‐stranded RNA of about 22 nt in length (Mohr & Mott, ). And it can reverse the expression of the objective gene by inhibiting the translation or degradation of objective genes.…”
Section: Discussionmentioning
confidence: 99%